Representation of Female Identity and Emotional Healing in Korean Drama “When Life Gives You Tangerines” in Indonesia - Oceanie, Lady Yusticia; Janah, Miftahul Nurul; Desfianti, Winda Galuh (Syntax Literate, 2025)
Korean wave or hallyu has grown very popular worldwide over the years, starting from its foods, culture, K-pop, K-movie, and K-drama. K-drama has become a source of entertainment for many people because of its actors and actresses, story line, and impeccable acting skill. Recently, both K-movie and K-drama have changed its cliche ‘poor girl and rich guy’ plot towards socio cultural issue, such as rich-poor gap issue in Oscar awarded movies Parasite, structural poverty in the hit Netflix series Squid Game, and most recent is When Life Gives You Tangerines where it tells a story about women in different generation struggling to survive. It is heavily focused on women as they face hardships and struggle to break the generational pain. This study applies Stuart Hall’s representation theory since audience’s responses are divided into relatable with the drama, relatable but to some extent, and not relatable at all. The scope of this study is in Indonesia, and employs a qualitative study by collecting data through questionnaire, textual analysis from some of the key episodes, and social media response analysis. The finding of this study is expected to contribute to the ongoing research on media studies, particularly within Asia and concentrate around women issues.